2004
DOI: 10.1007/s10201-004-0128-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dissolved organic carbon in lakes of different trophic types

Abstract: The distributions of dissolved organic carbon (DOC) in the warm season were elucidated in ten lakes of different trophic types in Japan, Russia, and China. DOC showed similar vertical distributions in all the lakes in summer when thermal stratification occurred. DOC in the epilimnion was higher than the value of 0.8 mg C l Ϫ1 found in the hypolimnion. In three Japanese lakes, hypolimnion DOC was negatively correlated with apparent oxygen utilization (AOU), reflecting the net oxidation of DOC using the dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…However, in lakes having low DOC concentrations (below 5.0 mg C l -1 ), the C : N ratios are low (approximately 12.2-15.1) and are similar to those of autochthonous algae and macrophytes (approximately 12). In oligo-and mesotrophic lakes such as Lake Biwa in this paper, in which DOC remains at low concentrations below several mg C l -1 (Sugiyama et al 2004), determining the nature of DOC is very difficult. Thus, developments of separate techniques relating to the chemical, physical, and biological characteristics of DOC are very important.…”
Section: Introductionmentioning
confidence: 99%
“…However, in lakes having low DOC concentrations (below 5.0 mg C l -1 ), the C : N ratios are low (approximately 12.2-15.1) and are similar to those of autochthonous algae and macrophytes (approximately 12). In oligo-and mesotrophic lakes such as Lake Biwa in this paper, in which DOC remains at low concentrations below several mg C l -1 (Sugiyama et al 2004), determining the nature of DOC is very difficult. Thus, developments of separate techniques relating to the chemical, physical, and biological characteristics of DOC are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Monteiro et al (2014) predicted DOC concentrations in an Amazonian black-water catchment using EC measures. Moreover, a significant positive correlation between DOC and EC was observed in both mesotrophic Lake Ikeda (Sugiyama et al 2004) and Yasu River (Mostofa et al 2007) in Japan. Large amounts of untreated wastewater from factories and residential areas are discharged into Chendonggang and Yincungang rivers (Yang et al 2012), a significant difference (n D 5, p D 0.04, two-tailed t-test) in EC was observed between lake center and Chendonggang River.…”
Section: Discussionmentioning
confidence: 96%
“…Large amounts of untreated wastewater from factories and residential areas are discharged into Chendonggang and Yincungang rivers (Yang et al 2012), a significant difference (n D 5, p D 0.04, two-tailed t-test) in EC was observed between lake center and Chendonggang River. Moreover, a positive relationship was apparent in Lake Taihu (n D 25, r D 0.5, p D 0.01), indicating that a fraction of DOC is input from the inflow rivers (Yoshioka et al 2002;Sugiyama et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several authors have reported an inverse correlation between DOC values and Secchi disk depths (Sugiyama et al, 2004;Aguilera et al, 2013), based on the reasonable assumption that high-DOC waters show elevated absorption of sunlight (Morris et al, 1995). In fact, the combination of absorbing material and suspended particles in high concentration would decrease the penetration of sunlight in the water column (Wetzel, 2001;Salmaso et al, 2007).…”
Section: Proxies For Dissolved Organic Carbon Concentration In Lakes mentioning
confidence: 99%